2008
DOI: 10.2353/ajpath.2008.070065
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Prostate Cancer Cellular Proliferation and Invasion by the Androgen Receptor Co-Activator ARA70β

Abstract: ARA70 was first identified as a gene fused to the ret oncogene in thyroid carcinoma and subsequently as a co-activator for androgen receptor (AR). Two isoforms of ARA70 have been identified: a 70-kDa version called ARA70␣ and an internally spliced 35-kDa variant termed ARA70␤. We have previously reported that ARA70␣ expression is reduced in prostate cancer, and its overexpression inhibits proliferation of LNCaP prostate cancer cells. However, the function of the ARA70␤ isoform in prostate cancer is not underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 35 publications
0
53
0
Order By: Relevance
“…NCOA4, YWHAE, ARL6IP1 and MINA are overexpressed in a number of different cancers (Hu et al 2004, Teye et al 2004, Cimino et al 2008, Peng et al 2008, Guo et al 2010. The up-regulation of YWHAE in breast cancer is associated with diseasefree and overall survival, and therefore, the downregulation of YWHAE from reduced PRMT6 levels may be unfavourable in relation to breast cancer prognosis (Cimino et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NCOA4, YWHAE, ARL6IP1 and MINA are overexpressed in a number of different cancers (Hu et al 2004, Teye et al 2004, Cimino et al 2008, Peng et al 2008, Guo et al 2010. The up-regulation of YWHAE in breast cancer is associated with diseasefree and overall survival, and therefore, the downregulation of YWHAE from reduced PRMT6 levels may be unfavourable in relation to breast cancer prognosis (Cimino et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These genes, taken from the list of 159 differentially expressed genes, comprised six genes with decreased expression and two with increased expression following PRMT6 knockdown. The genes were chosen for their biological significance and had relevance to either steroid hormone-dependent gene expression (FK506 binding protein 4, 59 kDa: FKBP4; homeodomain interacting protein kinase 3: HIPK3 and nuclear receptor co-activator 4: NCOA4) (Yeh & Chang 1996, Moilanen et al 1998, Riggs et al 2003 and/or cancer (NCOA4, ADP-ribosylation factor-like 6 interacting protein 1: ARL6IP1; MYC-induced nuclear antigen: MINA; tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein, epsilon polypeptide: YWHAE; phosphatase and tensin homolog: PTEN and insulin-like growth factor binding protein 3: IGFBP3) (Eng 2003, Hu et al 2004, Teye et al 2004, Cimino et al 2008, Peng et al 2008, Guo et al 2010, Ingermann et al 2010. PRMT6 levels were decreased in MCF-7 or T-47D breast cancer cells by siRNA for 48 h. We conducted further validation, utilising two (different) non-overlapping siRNAs targeting PRMT6 (individually) to decrease the likelihood of observing non-specific off-target effects.…”
Section: Prmt6 Influences Both Gene Activation and Repressionmentioning
confidence: 99%
“…Indeed, we showed that ARA70␤ functions as an oncogene in promoting prostate cancer cell growth and invasion. 20 In this study, we demonstrated that ARA70␣ functions as a tumor suppressor gene in prostate cancer in in vitro and in vivo experiments.…”
mentioning
confidence: 88%
“…ARA70␤ promotes androgen-dependent growth and invasion of prostate cell lines. 20 It appears that the changes in splicing of ARA70 into its two distinct variants may be a part of such an AR-dependent mechanism, which switches between either proliferation or growth arrest and/or differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation